ASSESSING THE IMPACT OF TEACHER L2 USE ON LEARNER SELF-EFFICACY PERCEPTIONS: THE CASE OF CHILEAN ELEMENTARY EFL LEARNERS - Cancino, Marco; Mera, Samantha (TEFLIN Journal, 2022)
Self-efficacy perceptions on second language settings have been linked to several aspects including learner performance in linguistic tasks, willingness to communicate, and language learning strategy use. These firmly place self-efficacy as a variable affecting cognitive and contextual aspects in language learning settings. However, the amount of L2 used by teachers needs to be researched in their own right, since an approach that makes the L2 compulsory in the language classroom may affect learners’ perceptions of their ability to learn the new language. This relationship becomes even more relevant in low-level EFL school settings where teachers are more willing to use the learners’ L1 in their lessons. Thus, to assess the impact of teacher L2 use on the self-efficacy of primary EFL learners, the present study investigated 58 Chilean 6th-grade EFL students’ self-efficacy beliefs in two contexts: L2-Only instruction (i.e., an approach where lessons are delivered solely in the L2), and L1-L2 instruction. Findings revealed that learners in the L2-Only group did not significantly decrease their self-efficacy when compared to the L1-L2 group, and that the L1-L2 group displayed significantly higher scores in the reading and writing components. It is argued that contextual aspects that include the nurturing of self-efficacy need to be considered to make informed decisions on whether to use the L1 and the L2 in the language classroom.